Gradually Increased Interhemispheric Functional Connectivity During One Night of Sleep Deprivation [Corrigendum] - Zhu Y (Dove Medical Press, 2021)
Zhu Y, Ren F, Zhu Y, et al. Nat Sci Sleep. 2020;12:1067–1074. The authors have advised that the name of last author on page 1067 is incorrect. Mingwen Zheng should be Minwen Zheng. The authors apologize for this error. Read the original article